Melt focusing along lithosphere–asthenosphere boundary below Axial volcano - G. M. Kent; A. F. Arnulf; S. C. Singh; H. Carton; A. J. Harding; S. Saustrup (Nature, 2025)
Abstract Beneath oceanic spreading centres, the lithosphere–asthenosphere boundary (LAB) acts as a permeability barrier that focuses the delivery of melt from deep within the mantle towards the spreading axis 1 . At intermediate-spreading to fast-spreading ridge crests, the multichannel seismic reflection technique has imaged a nearly flat, 1–2-km-wide axial magma lens (AML) 2 that defines the uppermost section of the LAB 3 , but the nature of the LAB deeper into the crust has been more elusive, with some clues gained from tomographic images, providing only a diffuse view of a wider halo of lower-velocity material seated just beneath the AML 4 . Here we present 3D seismic reflection images of the LAB extending deep (5–6 km) into the crust beneath Axial volcano, located at the intersection of the Juan de Fuca Ridge and the Cobb–Eickelberg hotspot. The 3D shape of the LAB, which is coincident with a thermally controlled magma assimilation front, focuses hotspot-related and mid-ocean-spreading-centre-related magmatism towards the centre of the volcano, controlling both eruption and hydrothermal processes and the chemical composition of erupted lavas 5 . In this context, the LAB can be viewed as the upper surface of a ‘magma domain’, a volume within which melt bodies reside (replacing the concept of a single ‘magma reservoir’) 6 . Our discovery of a funnel-shaped, crustal LAB suggests that thermally controlled magma assimilation could be occurring along this surface at other volcanic systems, such as Iceland.